The systematic techno-stylistic and chemical study of glass beads from post-15th century West African sites - Miriam Truffa Giachet; Bernard Gratuze; Denis Genequand; Yao Serge Bonaventure Loukou; Eric Huysecom; Anne Mayor (PLoS ONE, 2025)
The systematic chemical analysis of large collections of archaeological glass beads is essential to better understand trade patterns at different times around the world. Glass beads’ trade towards and within sub-Saharan West Africa grew exponentially over time to culminate with the establishment of the Atlantic Trade. Although these artefacts are very commonly found in archaeological contexts dating after the 15th century CE, the assemblages are generally poorly studied from a chemical point of view. We present here the study of 916 glass beads found in five archaeological sites in Ghana, Mali, and Senegal, in contexts dated between the 15th and the mid-20th century CE. Besides the techno-stylistic classification of the whole assemblage, the compositional study of a sub-group of 578 monochrome and polychrome glass beads was performed. The 798 glass samples composing the selected beads were therefore classified based on their main chemical composition. Moreover, major, minor, and trace elements analysis by Laser Ablation-Inductively Coupled Plasma-Mass Spectrometry (LA-ICP-MS) and the statistical analysis of the results by Principal Component Analysis (PCA) led to the identification of the probable origin of the glass. Different suppliers were distinguished for the Ghanaian earlier beads and the Senegalese and Malian later ones, in relation to the different European trade partners at different times.